THE DEFENSE OF JEAN-BAPTISTE GRENOULLE ON USING HIS MINORITY OF SENSE IN TOM TYKWER'S PERFUME: THE STORY OF A MURDERER MOVIE: PSYCHOANALYTIC APPROACH - APRILIA, WIDYA RATNA (2011)
This research is aimed to analyze defense of Jean-Baptiste Grenoulle on using his minority of sense in Tom Tykwer's Perfume: the Story of Murderer movie. The object of the study of this research is to analyze the film and the script based on its structural elements and the defense mechanism on the psychoanalytic perspective of the Perfume: the Story of Murderer movie. This research is a qualitative research. The data are taken from document analysis. The results of study as follows; the film created based on the set of time in 18th century French. So the element of the movie is character and characteristic suitable with the style of 18th-19th century. The plot and theme of the movie tells about the journey of Grenouille in a form of exposition story. The other technical elements also created based on the characteristic of the 18th-19th century. The defense mechanism of the major character only consists of sixes elements, such as: denial, displacement, intellectualization, reaction formation, regression, and sublimation. The denial of Grenouille appears when the first time Grenouille meets with Baldini. They often involve in many kinds of argumentation. The displacement happens on Grenouille when he is angry with Baldini because he lies with him by smashing the glass on the floor. The intellectualization of Grenouille appears when he was a kid, when his friend disturbs him, he is just quite and watches them and does nothing. The reaction formation of Grenouille appears when he tries to make a positive thinking by creating a fragrance perfume just to fulfill his obsession in perfume and not for himself. The regression and sublimation tells about the feeling of Grenouille, where sometimes he feels lonely, happy, and also scares and with a special capability in sensing many kinds of smells, he gets this capability since he was a kid until he grows up. Finally he uses his extraordinary capability on his work. Then he work as a perfume creator helped by